An Unusual Presentation of Liver Failure in a Patient with Primary Gastrointestinal Hodgkin's Lymphoma. (17th October 2010) - Rocque, Gabrielle B.; Malik, Jeffrey T.; Yang, David T.; Chang, Julie E.
Abstract : Introduction . Hodgkin's lymphoma (HL) presenting either with primary bowel involvement or with cholestasis is unusual. The combination of primary gastrointestinal HL presenting with cholestasis and ductopenia has not been previously described. Case Report . We present a case of primary gastrointestinal HL with evidence of liver involvement, but also with prominent ductopenia on liver biopsy and associated intrahepatic cholestasis. A 50-year-old man with a history of Crohn's disease presented with a bowel obstruction, for which he underwent a small bowel resection. Histology revealed HL. His course was complicated by cholestatic liver failure. A subsequent liver biopsy revealed both focal involvement by lymphoma and ductopenia, resembling vanishing bile duct syndrome (VBDS). He was treated with chemotherapy with improvement in his cholestasis, but he eventually succumbed due to further complications of his disease and treatment toxicities. Conclusion . This case of primary gastrointestinal HL associated with ductopenia does not meet classic criteria for VBDS, but the clinical presentation and pathology are suggestive of a VBDS-like paraneoplastic process. Therapies for HL in the setting of cholestatic liver failure require special consideration, but some reports of durable remissions and recovery of liver function have been reported.